Wiki Writing: Collaborative Learning in the College Classroom - Robert E. Cummingseauthor; Matt Barton (University of Michigan Press, 2008)
When most people think of wikis, the first—and usually the only—thing that comes to mind is Wikipedia. The editors of Wiki Writing: Collaborative Learning in the College Classroom, Robert E. Cummings and Matt Barton, have assembled a collection of essays that challenges this common misconception, providing an engaging and helpful array of perspectives on the many pressing theoretical and practical issues that wikis raise. Written in an engaging and accessible manner that will appeal to specialists and novices alike, Wiki Writing draws on a wealth of practical classroom experiences with wikis to offer a series of richly detailed and concrete suggestions to help educators realize the potential of these new writing environments.